Pengenalan Eco Print Guna Mengembangkan Keterampilan dan Kekreatifan Siswa - Septa Ardiyan M. Rohma; Elhefni; Dedi Sufriadi (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
The problem of waste, especially plastic waste, is a major challenge in maintaining environmental cleanliness and sustainability. Lack of awareness and knowledge of the community, especially students, in managing waste is the main cause of increasing pollution. Through a community service program at SMP N 54 Palembang, educational efforts were made by implementing a demonstration method in science learning to improve students' understanding of plastic waste management. This study used a qualitative descriptive approach, targeting grade VIII students. The results of the activity showed that the demonstration method was effective in guiding students to process plastic waste into useful craft products, such as bags from used detergent packaging. In addition to increasing environmental awareness and student creativity, this activity also has the potential to provide economic value. The application of this environmental-based contextual learning proves the importance of integrating environmental education in the teaching and learning process to create a generation that cares and is responsible for the environment.